Does the cultural consumption policy reduce carbon emission intensity in China? - Hongbin Yuan; Junchen Li; Zhijian Zhang (Humanities & Social Sciences Communications)
Abstract Cultural products are characterized by lower resource consumption, and promoting cultural consumption may raise awareness of and engagement in environmental sustainability. This study examines the impact of the Cultural Consumption Policy (CCP) on carbon emission intensity in China, using a dataset encompassing 280 Chinese prefecture-level cities from 2008 to 2019. The results of the difference-in-differences (DID) regression show that the CCP significantly reduces carbon emission intensity, with robust results across a series of robustness tests, including placebo tests and parallel trend tests. Further analysis provides evidence that the upgrading of industrial structure, both in terms of output and employment, and the increased resident consumption, are likely mechanisms contributing to our findings. The results emphasize the pivotal role of cultural industry development in mitigating carbon emission intensity and highlight the need for supportive policies that stimulate cultural consumption.